Red cell alloimmunization in pregnancy: a study from a premier tertiary care centre of Western India - Meenakshi Gothwal; Pratibha Singh; Archana Bajpayee; Neha Agrawal; Garima Yadav; Charu Sharma (Korean Society of Obstetrics and Gynecology, 2023)
Objective The study was conducted to determine the frequency of alloimmunization to various blood group antibodies in pregnant women, and the risk of hemolytic disease in the fetus and newborn. Methods All antenatal women, irrespective of the period of gestation or obstetric history, were included, whereas those taking anti-D immune-prophylaxis or with a history of blood transfusion were excluded. Antibody screening and identification were performed using a Bio-Rad ID microtyping system. Results Of 2,084 antenatal females, 1,765 were D-antigen positive and 319 D-antigen negative. Sixty-five (3.119%) women alloimmunized. Out of 54 (2.591%) who had sensitized to D-antigen, 11 (0.527%) also sensitized to other antibodies. These 11 alloantibodies identified included: anti-M (n=6; 9.23%), anti-C (n=1; 3.076%), anti-E (n=1; 1.538%), anti-e (n=1; 1.538%), anti-Lewis (a) (n=1; 1.538%), and unspecified antibodies (n=1; 1.538%). Multiple antibodies were seen in four patients that combined: anti-D and anti-C (n=2; 3.076%), anti-e and anti-c (n=1; 1.538%), and anti-D and anti-G (n=1; 1.538%). Conclusion The rate of alloimmunization in D-antigen-negative women was high. Apart from this, the alloimmunization rate in women with bad obstetric history was very high, at 8.1%. In developing countries such as India, universal antenatal antibody screening, though desirable, may not be justified at present, as the cost and infrastructure required would be immense because of the lower alloimmunization rates in RhD antigen-positive women. However, it is necessary to impose properly formulated protocols to screen pregnant women with bad obstetric history.